2008
DOI: 10.1016/j.aap.2008.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Road crashes involving animals in Australia

Abstract: Each year in Australia many thousands of collisions occur between motor vehicles and animals, resulting in considerable vehicle repair costs, injury to persons, and loss of animal life. This paper reviews animal-related road crashes in Australia and presents data from the in-depth Rural and Remote Road Safety Study in North Queensland for serious casualties (n=33) resulting from direct impact with an animal or swerving to avoid an animal on public roads. These crash types accounted for 5.5% of all eligible on-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
52
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(61 citation statements)
references
References 14 publications
5
52
0
3
Order By: Relevance
“…From the Queensland data (which was the most detailed), the period when the largest proportion of animal-vehicle collisions occurred was between 18:00 and 23:59 hours and most incidents occurred in 100-110 km h À1 speed zones (Queensland Transport 2007 in Rowden et al 2008). High proportions of these incidents were reported to involve kangaroos or wallabies: 47% in New South Wales and 45% in Queensland (Rowden et al 2008). Statistics on the type of animal involved from crashes in other states and territories were not reported.…”
Section: Human Aspects Of Macropod-vehicle Collisionsmentioning
confidence: 99%
See 2 more Smart Citations
“…From the Queensland data (which was the most detailed), the period when the largest proportion of animal-vehicle collisions occurred was between 18:00 and 23:59 hours and most incidents occurred in 100-110 km h À1 speed zones (Queensland Transport 2007 in Rowden et al 2008). High proportions of these incidents were reported to involve kangaroos or wallabies: 47% in New South Wales and 45% in Queensland (Rowden et al 2008). Statistics on the type of animal involved from crashes in other states and territories were not reported.…”
Section: Human Aspects Of Macropod-vehicle Collisionsmentioning
confidence: 99%
“…Further investigation into the variation across each year revealed that the mean length of natural darkness (time between sunset and sunrise) was positively correlated with the number of animal-related collisions (at the scale of month) and explained 89% of variation in crash rate (Ramp and Roger 2008). Rowden et al (2008) collated data on vehicle collisions with animals in Australia, with data from most states and territories covering the five-year period 2001-05. From the Queensland data (which was the most detailed), the period when the largest proportion of animal-vehicle collisions occurred was between 18:00 and 23:59 hours and most incidents occurred in 100-110 km h À1 speed zones (Queensland Transport 2007 in Rowden et al 2008).…”
Section: Human Aspects Of Macropod-vehicle Collisionsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Loss et al (2014), collisions between vehicles and animals kill hundreds of millions of birds and other animals each year. According to Rowden et al (2008), only in Australia more than 11,635 accidents happened between vehicles and animals in the time period of [2001][2002][2003][2004][2005]. According to Langbein (2007), 30,500 accidents happened in Brittan between deer and vehicles in the time period of 2000-2005.…”
Section: Species Basedmentioning
confidence: 99%
“…15 Specifically in relation to primates, most prefers forests in habitats usually far from humans, indeed, 90% of non-human primates are dependent on tropical forests Isabirye-Basuta & Lwanga, 16 and as occur with other animals, the proximity with humans generates disadvantages and some benefits. Specifically for primates, an important problem associate to them and involved in the humanswildlife relationship is the yellow fever, a disease that affects humans in different cycles, the sylvatic for the primates and urban for humans Costa et al 17 in fact, most vertebrates that host the yellow fever virus are primates, including humans Herve et al 18 Monath, 19 Vasconcelos.…”
mentioning
confidence: 99%